Effect of lactate consumption on exercise performance - Bryner, R. W.; Hornsby, W. G.; Chetlin, R.; Ullrich, I. H.; Yeater, R. A. (The Journal of Sports Medicine and Physical Fitness, 1998)
The effect of an 8% carbohydrate drink with and without an augmentation of 2% lactate solution was assessed on endurance performance, peak power, and delayed blood acidosis. Seven trained cyclists (M = 6; F = 1) performed four one-week-apart tests to exhaustion at an intensity of heart rate 10 bpm below maximum. VO2max, heart rate, and heart rate first associated with a respiratory exchange ratio that exceeded 1.0, were measured. The drinks were ingested 2-3 hours prior to each test. There were no differences in performance, physiological parameters, or blood factors between the carbohydrate-alone and carbohydrate-lactate conditions. Implication. Aerobic endurance exercise is unaffected by a lactate supplement added to carbohydrate drinks.